In Memory, Theory: Concluding Unscientific Postludes - Tulachan, Binu; Gardiner, Michael; Sakata, Jon (Current Musicology, 2013)
In a letter to a friend Leibniz likens the material (i.e. physical) effects of monadic (i.e. nonphysical) aggregates to the phenomenon of refraction/ diffraction in the perception of a rainbow. [monads are the nonphysical, nonspatial, metaphysical units, the ‘simple substances’ of Leibniz’s philosophical system] In much the same way light is prismatically dispersed through droplets of water in a mist, giving rise to an arc of spectral colors, for Leibniz matter is the result of a comparable monadic refraction. Bow, light, mist. All part of the same network. Baudrillard’s real chimera: the thing perceived already an aggregate effect. Buddhism’s real chimera: the skandhas (five aggregates) and the causal interplay of emptiness and form. Likewise, perception and appetition are obverses of an interdependent process; “Monads reach out confusedly to infinity, to everything, but they are restricted and distinguished from each other by the degrees of distinctness of their perceptions” (Leibniz, Monadology § 60).